Changes in weather pattern affect insect composition in Madai, Sabah. - M.Y. Meriam (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Biodiversity can be studied at a species level such as insect group. Insects play important roles in the ecosystem which is affected by the climate factors such as rainfall pattern, humidity and temperature. Changes on this climate pattern might give direct and indirect impacts on the insect activities as the global trend of climate showed a warmer effect which has caused the glacier to melt faster withless ice coverage, the rise at the sea level and the global temperature continues to rise in the future. Glacier has lost ice coverage tremendously. The sea level also reported rise up and the temperature predicted continuously increased. This study was carried out at Cocoa Research and Development Centre (CRDC) Madai, Sabah, Malaysia. The objective of this study was to examine the impacts of weather pattern changes on the insect composition in the last 11 years. This study was carried out at three different areas using four different insect trapping methods such as pitfall trap, winkler trap, line transet trap and light trap. Result from this study showed that the insect composition has changed drastically in the last 11 years.  Reduction in number of insect catched using 4 different methods has suggested that the changes in weather pattern over period of time have some effects on insect composition.